Right Coronary Artery Originated from the Left Anterior Descending Artery in a Patient with Congenital Pulmonary Valvular Stenosis - Yusuf Hoşoğlu; Cihan Örem; Oğuzhan Ekrem Turan; Mustafa Öztürk; Ömer Gedikli; Ayşe Hoşoğlu; Mürsel Şahin (Case Reports in Cardiology)
The single coronary artery, anomalous origin of the right coronary artery from the left anterior descending artery, is a benign and very rare coronary artery anomaly. We firstly present a case with this type of single coronary artery and congenital pulmonary valvular stenosis with large poststenotic dilatation.